ANALISA SISTEM INFORMASI KEAMANAN INTERNET SPEEDY PADA PLASA TELKOM TANJUNGBALAI - Khairul Saleh; Tini Fitriani ((JurTI) Jurnal Teknologi Informasi, 2017)
Abstrack - The application of information technology at this time is very closely related to everyday life. Komunikas which at first was only conveyed in a very simple way, namely "mouth by mouth" (coming directly between one human and another). In addition, the speedy internet network security system is also used as a process to prevent and identify unauthorized users (intruders) from the internet network. The aim is to anticipate the risk of internet networks that can be either physical or logical threats. What is meant by physical threat is that can damage the physical part of the computer or computer hardware while the threat of logic is in the form of theft of data or intruders who break into someone's account.   Keywords - Security System, Speedy Network